2020
DOI: 10.1158/1541-7786.mcr-19-0974
|View full text |Cite
|
Sign up to set email alerts
|

27-Hydroxycholesterol Impairs Plasma Membrane Lipid Raft Signaling as Evidenced by Inhibition of IL6–JAK–STAT3 Signaling in Prostate Cancer Cells

Abstract: We recently reported that restoring the CYP27A1–27hydroxycholesterol axis had antitumor properties. Thus, we sought to determine the mechanism by which 27HC exerts its anti–prostate cancer effects. As cholesterol is a major component of membrane microdomains known as lipid rafts, which localize receptors and facilitate cellular signaling, we hypothesized 27HC would impair lipid rafts, using the IL6–JAK–STAT3 axis as a model given its prominent role in prostate cancer. As revealed by single molecule imaging of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…The IL6-JAK-STAT3 pathway, known to be an important signaling pathway in prostate cancer, requires intact lipid rafts for sustaining pro-oncogenic signaling. Also in this case, disruption of lipid rafts by MβCD inhibited this pathway thus controlling prostate cancer growth (Dambal et al, 2020). In addition, it has also been reported that hypoxia, a prognostic predictor of poor clinical outcome (Vaupel et al, 2001), was able to increase cholesterol level and recruitment of Notch3 into lipid rafts.…”
Section: Raft-associated Cholesterol Involvement In Migration Invasimentioning
confidence: 64%
“…The IL6-JAK-STAT3 pathway, known to be an important signaling pathway in prostate cancer, requires intact lipid rafts for sustaining pro-oncogenic signaling. Also in this case, disruption of lipid rafts by MβCD inhibited this pathway thus controlling prostate cancer growth (Dambal et al, 2020). In addition, it has also been reported that hypoxia, a prognostic predictor of poor clinical outcome (Vaupel et al, 2001), was able to increase cholesterol level and recruitment of Notch3 into lipid rafts.…”
Section: Raft-associated Cholesterol Involvement In Migration Invasimentioning
confidence: 64%
“…We found that LCD reversed the ADT-reduced acyl-carnitines and the increased acyl-carnitines were strongly clustered with increased ketone-related metabolites. 49,50 Together, these findings suggest a metabolic connection between ketogenesis and altered acyl-carnitines, indicating the ability of LCD to reverse these ADTinduced metabolic changes.…”
Section: Discussionmentioning
confidence: 81%
“…However, another oxysterol of enzymatic origin, namely 27-hydroxycholesterol (27OHC), is gaining increasing consideration as a protective molecule not only against the respiratory virus Rhinovirus, but also against a wide range of other viral infections [ [8] , [9] , [10] , [11] ]. There is clear evidence that exogenously added 27OHC accumulates in plasma membrane lipid rafts, likely affecting viral entry but also modulating cell signaling stemming from such microdomains [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%